KONSEP RAḌĀ’AH DALAM AL-QURAN: Kajian Tafsir Tematik Ayat-Ayat Tentang Menyusui Bayi Dalam Perspektif Mufassir Dan Sains - Masrul Isroni Nurwahyudi (QOF, 2017)
This paper studied about how the Qur’anic view of the concept of breastfeeding through the interpretation of QS al-Baqarah (2): 233, and QS al-Thalāq (65): 6. To get Comprehensive analysis results, the writer used thematic tafsir as research methodology. The writer tried to relate it to psychological aspects as supporting argument for the hadith information. The concept of breastfeeding in the maximal Qur’an concerns the following: the meaning of radla’ah, the definition of al-walidat, the law of breastfeeding, the duration of breastfeeding, and the provision of the livelihood that should be given to the wife. Like the wisdom of the rad command (a’ah) which Allah calls for in the Qur’an for the disciples to breastfeed their children for two years that is because God knows about the times that a baby needs the love of a mother. At that time the baby is still creating the physical, psychological, social and spiritual aspect. In order for parents are able to carry out God’s mandate, then surely the baby will grow and develop with healthy conditions physically and spiritually. This was also supported by findings on breastfeeding problems from a medical and psychiatric perspective. Breastfeeding will provide an opportunity for babies to grow into humans who have more stable emotions and better social development. Breast milk is an important food and the only source of life for babies in the first months of life. The best milk for children is breast milk because with breastfeeding comes the contact of love and affection between mother and child. Mother is the one who is most able to give love and real warmth to the child with her motherly instinct given by God sed.